Modelling the effects of forest management intensification on base cation concentrations in soil water and on tree growth in spruce forests in Sweden - Zanchi, Giuliana; Lucander, Klas; Kronnäs, Veronika; Lampa, Martin Erlandsson; Akselsson, Cecilia (European Journal of Forest Research, 2021)
Abstract The study investigated the effects of forest residue extraction on tree growth and base cations concentrations in soil water under different climatic conditions in Sweden. For this purpose, the dynamic model ForSAFE was used to compare the effects of whole-tree harvesting and stem harvesting on tree biomass and the soil solution over time at 6 different forest sites. The study confirmed the results from experimental sites showing a temporary reduction of base cation concentration in the soil solution for a period of 20–30 years after whole-tree harvesting. The model showed that this was mainly caused by the reduced inputs of organic material after residue extraction and thereby reduced nutrient mineralisation in the soil. The model results also showed that whole-tree harvesting can affect tree growth at nitrogen-poor forest sites, such as the ones in northern Sweden, due to the decrease of nitrogen availability after residue removal. Possible ways of reducing this impact could be to compensate the losses with fertilisation or extract residue without foliage in areas of Sweden with low nitrogen deposition. The study highlighted the need to better understand the medium- and long-term effects of whole-tree harvesting on tree growth, since the results suggested that reduced tree growth after whole-tree harvesting could be only temporary. However, these results do not account for prolonged extraction of forest residues that could progressively deplete nutrient pools and lead to permanent effects on tree growth.